How common are ALS plateaus and reversals?. (1st March 2016) - Bedlack, Richard S.; Vaughan, Timothy; Wicks, Paul; Heywood, Jamie; Sinani, Ervin; Selsov, Roger; Macklin, Eric A.; Schoenfeld, David; Cudkowicz, Merit; Sherman, Alex
Abstract : Objective: To determine the frequency of amyotrophic lateral sclerosis (ALS) plateaus and reversals in the Pooled Resource Open-Access ALS Clinical Trials (PRO-ACT) database. Methods: We analyzed Amyotrophic Lateral Sclerosis Functional Rating Scale (ALSFRS) and ALSFRS–revised (ALSFRS-R) data from PRO-ACT participants. The frequencies of participants experiencing plateaus (periods where scores did not change) were calculated over 6-, 12-, and 18-month epochs. The percentage of participants ever experiencing reversals (periods where scores improved) of different lengths were also calculated and plotted. Results: Over 6 months, 25% of 3, 132 participants did not decline. Over 12 months, 16% of 2, 105 participants did not decline. Over 18 months, 7% of 1, 218 participants did not decline. Small ALS reversals were also common, especially over shorter follow-up intervals; 14% of 1, 343 participants had a 180-day interval where their ALSFRS-R slope was greater than zero. Fewer than 1% of participants ever experienced improvements of 4 or more ALSFRS-R points lasting at least 12 months. Conclusion: ALS plateaus and small reversals are common, especially over brief intervals. In light of these data, stable disease, especially for a short period of time, should not be interpreted as an ALS treatment effect. Large sustained ALS reversals, on the other hand, are rare, potentially important, and warrant further study.